Expression GWAS of PGIP1 Identifies STOP1-Dependent and STOP1-Independent Regulation of PGIP1 in Aluminum Stress Signaling in Arabidopsis - Agrahari, Raj Kishan; Enomoto, Takuo; Ito, Hiroki; Nakano, Yuki; Yanase, Emiko; Watanabe, Toshihiro; Sadhukhan, Ayan; Iuchi, Satoshi; Kobayashi, Masatomo; Panda, Sanjib Kumar; Yamamoto, Yoshiharu Y.; Koyama, Hiroyuki; et al. (Frontiers in Plant Science, 2021)
To elucidate the unknown regulatory mechanisms involved in aluminum (Al)-induced expression of POLYGALACTURONASE-INHIBITING PROTEIN 1 (PGIP1), which is one of the downstream genes of SENSITIVE TO PROTON RHIZOTOXICITY 1 (STOP1) regulating Al-tolerance genes, we conducted a genome-wide association analysis of gene expression levels (eGWAS) of PGIP1 in the shoots under Al stress using 83 Arabidopsis thaliana accessions. The eGWAS, conducted through a mixed linear model, revealed 17 suggestive SNPs across the genome having the association with the expression level variation in PGIP1. The GWAS-detected SNPs were directly located inside transcription factors and other genes involved in stress signaling, which were expressed in response to Al. These candidate genes carried different expression level and amino acid polymorphisms. Among them, three genes encoding a NAC domain-containing protein 27 (NAC027), a TRX superfamily protein, and an R-R-type MYB protein were associated with the suppression of PGIP1 expression in their mutants, and accordingly, the system affected Al tolerance. We also found the involvement of Al-induced endogenous nitric oxide (NO) signaling, which induces NAC027 and R-R-type MYB genes to regulate PGIP1 expression. In this study, we provide genetic evidence that STOP1-independent NO signaling pathway, and STOP1-dependent regulation in phosphoinositide (PI) signaling pathway are involved in the regulation of PGIP1 expression under Al stress.